2013
DOI: 10.29047/01225383.48
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Dispersion Gels (CDG) to improve volumetric sweep efficiency in waterflooding processes

Abstract: Aviable option for the sustainability of hydrocarbon supply in the short and medium term is increasing the expected ultimate oil recovery factor through Enhanced Oil Recovery processes (EOR). f .The purpose of this paper is to describe a methodology to evaluate EOR technologies developed at the Instituto Colombiano del Petróleo (ICP) of ECOPETROL S.A. in 2012. The methodology includes theoretical evaluation, design (geological analysis, engineering analysis, laboratory static and dynamic tests and numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Colloidal dispersion gels (CDGs) are in situ gel aggregates that are formed by low polymer concentration (100–1000 mg/L) of high molecular weight (usually more than 22 million Dalton) anionic HPAM, and aluminum citrate or chromic citrate as the cross-linker. , The cross-linking type of this process is dominated by intramolecular cross-linking effect. The solution contained separate and suspended gel aggregates that are nearly spherical particles with particle sizes ranging from 1 to 150 nm. Temperature resistance of this kind of gel system is mainly decided by the properties of the polymer. Spildo et al reported that CDGs could be prepared at 85 °C and below 35000 mg/L.…”
Section: In Situ Cross-linked Polymer Gelsmentioning
confidence: 99%
“…Colloidal dispersion gels (CDGs) are in situ gel aggregates that are formed by low polymer concentration (100–1000 mg/L) of high molecular weight (usually more than 22 million Dalton) anionic HPAM, and aluminum citrate or chromic citrate as the cross-linker. , The cross-linking type of this process is dominated by intramolecular cross-linking effect. The solution contained separate and suspended gel aggregates that are nearly spherical particles with particle sizes ranging from 1 to 150 nm. Temperature resistance of this kind of gel system is mainly decided by the properties of the polymer. Spildo et al reported that CDGs could be prepared at 85 °C and below 35000 mg/L.…”
Section: In Situ Cross-linked Polymer Gelsmentioning
confidence: 99%
“…Chromium triacetate is used in fields with a high salinity of reservoir water. The polymer-to-crosslinker ratio may vary from 20:1 to 80:1 [ 95 ].…”
Section: Methodsmentioning
confidence: 99%
“…These agents can be classified into two broad categories: in situ prepared agents and preformed agents. In situ prepared agents include colloidal dispersion gels (CDGs) [ 5 , 6 ], linked polymer solutions (LPSs) [ 7 , 8 ], etc. Preformed agents include dispersed particle gels (DPGs) [ 9 , 10 , 11 ], preformed particle gels (PPGs) [ 12 , 13 ], polymer microspheres (PMs) [ 14 , 15 , 16 ], etc.…”
Section: Introductionmentioning
confidence: 99%